Radar and optical remote sensing for near real‐time assessments of cyclone impacts on coastal ecosystems. Issue 4 (14th February 2022) - Mondal, Pinki; Dutta, Trishna; Qadir, Abdul; Sharma, Sandeep
Abstract: Rapid impact assessment of cyclones on coastal ecosystems is critical for timely rescue and rehabilitation operations in highly human‐dominated landscapes. Such assessments should also include damage assessments of vegetation for restoration planning in impacted natural landscapes. Our objective is to develop a remote sensing‐based approach combining satellite data derived from optical (Sentinel‐2), radar (Sentinel‐1), and LiDAR (Global Ecosystem Dynamics Investigation) platforms for rapid assessment of post‐cyclone inundation in non‐forested areas and vegetation damage in a primarily forested ecosystem. We apply this multi‐scalar approach for assessing damages caused by the cyclone Amphan that hit coastal India and Bangladesh in May 2020, severely flooding several districts in the two countries, and causing destruction to the Sundarban mangrove forests. Our analysis shows that at least 6821 sq. km. land across the 39 study districts was inundated even after 10 days after the cyclone. We further calculated the change in forest greenness as the difference in normalized difference vegetation index (NDVI) pre‐ and post‐cyclone. Our findings indicate a <0.2 unit decline in NDVI in 3.45 sq. km. of the forest. Rapid assessment of post‐cyclone damage in mangroves is challenging due to limited navigability of waterways, but critical for planning of mitigation and recovery measures. We demonstrate the utility of Otsu method, an automated statistical approach of the Google Earth Engine platform to identify inundated areas within days after a cyclone. Our radar‐based inundation analysis advances current practices because it requires minimal user inputs, and is effective in the presence of high cloud cover. Such rapid assessment, when complemented with detailed information on species and vegetation composition, can inform appropriate restoration efforts in severely impacted regions and help decision makers efficiently manage resources for recovery and aid relief. We provide the datasets from this study on an open platform to aid in future research and planning endeavors. Abstract : In this paper, we present a remote sensing based approach combining satellite data derived from optical (Sentinel‐2), radar (Sentinel‐1), and LiDAR (Global Ecosystem Dynamics Investigation) platforms for near real‐time assessment of post‐cyclone inundation and vegetation damage. We demonstrate the applicability of this multi‐scalar approach for cyclone Amphan that hit coastal India and Bangladesh in May 2020, severely flooding several districts in the two countries, and causing destruction to the Sundarban mangrove forests. We envision our open access high‐resolution data and methods to be of great interest to decision makers and conservation scientists.